2019
DOI: 10.1089/wound.2018.0806
|View full text |Cite
|
Sign up to set email alerts
|

Honey-Based Salve and Burdock Leaf Dressings as an Alternative to Surgical Debridement of a Traumatic Wound Eschar

Abstract: Objective: Nonviable necrotic eschar is an impedance to wound healing and can ultimately lead to failure of soft tissue coverage in traumatic or high-risk wounds. Topical therapeutic agents can provide a less invasive management alternative to surgical debridement of eschar.Approach: The case of a 40-year-old male with a traumatic right lower extremity amputation complicated by surgical incision ischemic eschar formation is reported. Honey-based salve with burdock leaf dressings was used to noninvasively manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The present histopathological results revealed that all honey treated septic wounds had different re-epithelization process indicating variant healing potencies (figures [5][6][7][8][9][10][11][12][13][14] Wound healing is a complex and systematic process, in terms of histopathology it includes three phases including inflammation, proliferation, and remodeling [58]. Honey increases activity of fibroblasts [29] and collagen formation [20,59].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present histopathological results revealed that all honey treated septic wounds had different re-epithelization process indicating variant healing potencies (figures [5][6][7][8][9][10][11][12][13][14] Wound healing is a complex and systematic process, in terms of histopathology it includes three phases including inflammation, proliferation, and remodeling [58]. Honey increases activity of fibroblasts [29] and collagen formation [20,59].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the renewed wound healing activity of honey is widely documented [9,13,14], even with infected [3,15], or non-healing wounds resulting in faster healing process, wound size reduction and lower pain intensity [16]. The present study aimed to investigate the potency of different types of honey as wound dressing for septic skin wounds at limb distal regions in donkeys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation